Pengaruh Keterampilan Membaca Teks Bahasa Arab terhadap Keterampilan Berbicara Bahasa Arab pada Siswa Kelas V-A KMI Pondok Pesantren Baitul Hidayah Bandung Tahun Ajaran 2024/2025 - Farhan Abdillah Fasya; Ifa Rodifah Nur (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study is motivated by the importance of the relationship between reading and speaking skills in Arabic language learning. Reading, as a receptive skill, plays a significant role in enriching vocabulary, understanding language structures, and constructing meaning, which in turn affects speaking ability as a productive skill. At Baitul Hidayah Islamic Boarding School in Bandung, variations were observed in students’ abilities in reading Arabic texts and speaking Arabic, raising questions about the existence of a relationship between these two skills. This study aims to determine whether there is an influence of Arabic reading skills on Arabic speaking skills among fifth-grade students (Class V-A) in the 2024/2025 academic year. This research employs a quantitative approach with a correlational design. The subjects of the study consisted of all 28 students in Class V-A, selected using a saturated sampling technique. Data were collected through reading skill tests and speaking skill tests, and subsequently analyzed using descriptive statistics and the Spearman rank correlation test. The results indicate a significant relationship with a strong level of correlation between Arabic reading skills and Arabic speaking skills. This is evidenced by the correlation coefficient (r-value) of 0.824, which is higher than the r-table value at a 5% significance level (0.374). It is recommended that the development of reading skills be more systematically integrated with speaking practice. Further research is suggested to involve a larger sample size and more diverse variables to strengthen the findings.